Effect of Labor Camera on the Duration of the Second Stage Labor in Primipara - Yetti Purnama; Kurnia Dewiani; Linda Yusanti (Universitas Islam Bandung, 2021)
Fear and anxiety due to severe labor pains could also lead to prolonged labor. The efforts made to accelerate the second stage labor process are by providing emotional support with the support of a labor camera. The mother is allowed to observe the development state of her baby's head through video on a tablet or laptop screen. Furthermore, the mother's emotional level becomes more provoked and motivated to strain the labor process faster. This study aims to determine the effect of the labor cameras on the second state duration in primiparous. The design of this study was a posttest-only control group design experiment with a total sample of 30 primiparous of the second stage at independent midwife practice in Bengkulu city in November–December 2020. Each group consisted of 15 for treatment (with labor cameras) and 15 for control (without labor cameras)—the assessment of the labor duration by counting the labor time in seconds during the second state. The statistical results using the t test and chi-square test analysis showed that the intervention group's labor duration (1,393.3 seconds) was shorter than the control group's (2,340.6 seconds). The mean difference in the delivery time was 947.3 seconds or 15.7 minutes faster in the intervention group than in the control group. In conclusion, using a labor camera on the labor duration of the second stage in primiparous mothers is an effect of using a labor camera. PENGARUH KAMERA PERSALINAN TERHADAP DURASI PERSALINAN KALA II PADA PRIMIPARARasa takut dan cemas akibat nyeri persalinan yang berat juga dapat menyebabkan partus lama. Salah satu upaya yang dilakukan untuk mempercepat proses kala II persalinan adalah memberikan dukungan emosional dengan bantuan kamera persalinan. Ibu diberi kesempatan untuk melihat perkembangan pengeluaran kepala bayinya melalui video pada layar tablet atau laptop sehingga tingkat emosional ibu menjadi lebih terbangun dan termotivasi untuk mempercepat proses persalinan. Penelitian ini bertujuan mengetahui pengaruh kamera persalinan terhadap durasi persalinan kala II pada primipara. Desain penelitian adalah eksperimen posttest-only control group design dengan jumlah sampel 30 primipara kala II di bidan praktik mandiri Kota Bengkulu pada November–Desember 2020. Tiap-tiap kelompok berjumlah 15 untuk kelompok perlakuan (menggunakan kamera persalinan) dan 15 untuk kontrol (tidak menggunakan kamera persalinan). Penilaian durasi persalinan dengan menghitung detik selama kala II berlangsung. Pengujian statistik menggunakan analisis uji t dan uji chi-square menunjukkan bahwa durasi persalinan kelompok perlakuan (1.393,3 detik) lebih singkat daripada kelompok kontrol (2.340,6 detik). Selisih perbedaan waktu persalinan rerata selama 947,3 detik atau 15,7 menit lebih cepat pada kelompok intervensi dibanding dengan kelompok kontrol. Simpulan, terdapat pengaruh penggunaan kamera persalinan terhadap durasi persalinan kala II pada ibu primipara.